Relationship of Nutritional Status and Food Consumption with the Biochemical Profile in Diabetes Mellitus Carriers of Type 2 of a Municipal Vale do Taquari - RS (Global Journal of Medical Research, 2020)
This study aimed to relate the nutritional status and food consumption with the biochemical profile of patients with type 2 diabetes mellitus (DM2), who attended Health Education groups promoted by a Basic Health Unit in the city of Rio Grande do Sul, Brazil. Quantitative, cross-sectional study, with a sample of 74 adult and elderly individuals. Data collection corresponded to the measurement of anthropometric measurements of weight and height, waist circumference (WC, arm circumference (CB), neck circumference (CP), tricipital skin fold (PCT) and subscapular skin (PCS), application of a 24-hour food record, referring to a day of the week and a food record of a day of the weekend, and biochemical data of the blood.
Keywords: diabetes mellitus nutritional assessment health center